The Cost of Medicaid Savings: The Potential Detrimental Public Health Impact of Neonatal Circumcision Defunding. (18th October 2012) - Andrews, Annie L.; Lazenby, Gweneth B.; Unal, Elizabeth Ramsey; Simpson, Kit N.
Abstract : Objective . To project the increased incidence of HIV and subsequent costs resulting from the expected decreased rate of circumcision due to Medicaid defunding in one southeastern state. Methods . Using 2009 South Carolina (SC) Medicaid birth cohort (n = 29, 316 ), we calculated expected heterosexually acquired HIV cases at current circumcision rates. To calculate age/race/gender specific HIV incidence rates, we used 2009 South Carolina Department of Health and Environmental Control reported gender and race specific HIV cases, CDC reported age distribution of HIV cases, and 2009 S.C. population data. Accounting for current circumcision rates, we calculated the change in incidence of heterosexually acquired HIV assuming circumcision provides 60% protection against HIV transmission to males and 46% protection against male to female transmission. Published lifetime cost of HIV was used to calculate the cost of additional HIV cases. Results . Assuming Medicaid circumcision rates decrease from current nationally reported levels to zero secondary to defunding, we project an additional 55 male cases of HIV and 47 female cases of HIV among this birth cohort. The total cost discounted to time of infection of these additional HIV cases is 20, 924, 400 for male cases and 17, 711, 400 for female cases. The cost to circumcise males in this birth cohort at currently reported rates is 4, 856, 000. Conclusions . For every year of decreased circumcision rates due to Medicaid defunding, we project over 100 additional HIV cases and 30, 000, 000 in net medical costs.